Eye-glasses wear compliance following school-based visual acuity screening in Nepal: a comparative study - Thapa, Hari Bahadur; Rai, Salma KC; Thapa, Saraswati Khadka; Khatri, Anadi; Bassett, Ken (Nepalese Journal of Ophthalmology, 2020)
Introduction: Eye-glasses wear compliance is found to be low among children in school-based eye screening programs who are provided spectacles free of charge. Methods: Thirty-six schools from school visual acuity screening program in Nepal were randomly selected to receive no follow-up (standard) or follow-up by an optometry team at 3 months. In the intervention group (that received the follow-up), ophthalmic personal made unannounced visits to the schools at 3 months to determine spectacle compliance .Direct examination to determine compliance with spectacle wear 6 months was done. The primary reason for noncompliance from a list of possibilities was identified using a questionnaire. Results: Among 297 (145 control and 152 intervention) students that received glasses in the 36 schools, 128/152 (84%) were available for examination at 3 months in the intervention group. A total of 216/297 (73%) students were available for examination at 6 months (73 % and 72% of the control and intervention groups, respectively). Within the intervention group, 51% of children at 3 months and 57% at 6 months were wearing glasses during the unannounced visits. The main source of refractive error was myopia. Out of 66 children with astigmatism, 24 (36%) were wearing glasses. There was no statistically significant difference in compliance (p=0.85) between private and public schools, but compliance correlated better with the educational status of careers. Conclusion: A follow-up visit to the school by eye care personnel did not improve spectacle wear compliance among children .Other factors may also be responsible for poor compliance.